Frequency of bullying perceived in clinical practices of last year interns of a medicine school: cross sectional study (2016)
Introduction: During the medical internship year, students attend several hospitals and are observed and influenced by postgraduate students, general practitioners and other interns, who provide them with fundamental support regarding professional training. Bullying is defined as an aggressive behavior that occurs between a perpetrator and a victim in different scenarios and authority relationships, such as clinical practices at Medicine programs.Objective: To describe the perceived frequency of bullying among a group of interns of the Faculty of Medicine from Universidad Nacional de Colombia during internship.Materials and methods: A transversal analytical study was performed through a questionnaire applied to 82 medical interns of the School of Medicine from Universidad Nacional de Colombia.Results: The perceived frequency of bullying was 90%. Statistically significant differences were not found in the stratified analysis by sex or place of practice. In most cases, bullying was perpetrated by other interns, while residents and specialists showed a lower frequency.Conclusion: Perceived frequency of bullying was higher than expected according to the existing literature. These results can be used as a basis for new studies.